Relasi Nasionalisme dan Islam dalam Lirik Syair Ya Lal Wathan - Abdur Rosid (Publikasi Indonesia, 2022)
The values ​​of nationalism and religion contained in the lyrics of the march of Syubbanul wathan or commonly called Ya Lal Wathan with the title